Threshold concept acquisition in occupational therapy: A mixed methods study of students and clinicians. (17th July 2019) - Nicola‐Richmond, Kelli; Pépin, Geneviève; Larkin, Helen; Mohebbi, Mohammedreza
Abstract : Background/aim: Demand for occupational therapy graduates able to work in complex and diverse workplaces is increasing. The threshold concepts framework has emerged as one pathway to assist in the development of work‐ready graduates. A previous Australian study identified 10 threshold concepts for occupational therapy; the aim of this study was to explore the acquisition of these. Method: A mixed‐methods study using observational, cross sectional design and a triangulation design convergence model was undertaken. A survey using Likert scales and open response questions was developed by the authors. Seventy‐three surveys were completed by 13 first and 20 final year Victorian occupational therapy students. Twenty recent graduates and 20 experienced clinicians from across Australia also participated. Seven first and 10 final year occupational therapy students, 10 recent graduates and 10 experienced clinicians also took part in in‐depth interviews. Likert scales were used by participants to rate confidence that they had acquired the threshold concepts, they also answered open‐response questions (via survey or interview) asking them to provide examples of how they would use threshold concepts in practice. Results: Fourth year students were statistically significantly less confident than experienced clinicians for the threshold concepts Understanding the models and theories of occupational therapy and Applying clinical reasoning ( P  < 0.05). When whole group data were analysed, participants were most confident for Occupation and Client centred practice ( P  < 0.05). These results resonated with the qualitative findings which demonstrated a shift from surface to deep knowledge with increased experience. Fourth year students reported responses that suggested some threshold concepts were still in development, while experienced clinicians used a web of threshold concepts. Conclusion: This exploratory study provides provisional data to suggest that students appear to still be acquiring some threshold concepts at graduation and experienced clinicians make use of a web of threshold concepts in their clinical practice.